Metal Biosorption Studies to Treat Combined Industrial Effluents Using P. chrysosporium - Sripathi Rao K; Ravindra P (ASEAN Journal of Chemical Engineering, 2006)
This work reports the treatability studies conducted on the combined industrial effluent sample by white rot fungus. The selected strain, Phanerochaete chrysosporium, a white rot fungus, was employed in reduction of toxic metals. The specific growth rate of the fungus was found to be in the range of 0.089 - 0.102 hr -1. Studies conducted on biosorption of metals showed that the dead fungal biomass was found to be more effective than living fungus. The optimum pH for the fungal growth was found to be at 4.5 but enhanced biosorption was at pH 6, especially for maximum reduction of hexavalent chromium to trivalent chromium. Laboratory-scale experiments for metal biosorption with this Basidiomycete showed encouraging results, which could be applied further to pilot tests and large-scale studies.